1996
DOI: 10.3109/08977199609003225
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of Placenta Growth Factor (PlGF) in Human Term Placenta

Abstract: Placenta growth factor (PlGF) is a growth factor which belongs to the vascular endothelial growth factor (VEGF) family and is known to bind to the fms-like tyrosine kinase receptor (flt-1). Using Western blot analysis a 50 kDa band was identified in placental protein extract which corresponded to PlGF homodimer. Immunoreactive PlGF was localised to the vasculosyncytial membrane and in the media of large blood vessels of the placental villi, while staining within the mesenchyme was weak and diffuse. There was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
1
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(99 citation statements)
references
References 15 publications
2
93
1
3
Order By: Relevance
“…The term placenta, which is large in size and thus has a large surface area of trophoblast, contained a consistently strong signal for PlGF mRNA. Khaliq et al (1996) and Vuorela et al (1997) also found PlGF mRNA in the term villus but did not investigate other stages of pregnancy. The abundant PlGF mRNA is likely to lead to significant quantities of PlGF protein being produced, and this is confirmed by the fact that immunoreactive PlGF can readily be detected in maternal circulation during pregnancy (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The term placenta, which is large in size and thus has a large surface area of trophoblast, contained a consistently strong signal for PlGF mRNA. Khaliq et al (1996) and Vuorela et al (1997) also found PlGF mRNA in the term villus but did not investigate other stages of pregnancy. The abundant PlGF mRNA is likely to lead to significant quantities of PlGF protein being produced, and this is confirmed by the fact that immunoreactive PlGF can readily be detected in maternal circulation during pregnancy (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Human PlGF is essentially expressed in the placenta, 26 more precisely in the syncytiotrophoblast. 1 PlGF is a potent stimulator of placental angiogenesis. 3,27 These new data provide 1 mechanism by which biomechanical forces induced by maternal blood flow, that is FSS, could modulate the angiogenic potential of the syncytiotrophoblast.…”
Section: Discussionmentioning
confidence: 99%
“…1 PlGF is a member of the vascular endothelial growth factor (VEGF) family and is crucial in initiating and perpetuating placental angiogenesis. 2 PlGF also induces vasodilation of uterine and myometrial arteries contributing to uterine vascular remodeling 3 and is associated with the systemic maternal cardiovascular adaptations to pregnancy.…”
mentioning
confidence: 99%
“…Recently, it has been proposed that serial determinations of the concentrations of sVEGFR-1 [38,39], PlGF [38], and s-Eng [39] are more informative in assessing the risk for PE than are single measurements in the first or second trimester. This is plausible because PlGF, s-Eng, and sVEGFR-1 are produced by the trophoblast [23,[39][40][41][42][43][44] and, therefore, maternal plasma concentrations can change with placental development from the first to the second trimester.…”
mentioning
confidence: 99%